The effect of coriander and fennel fruits on the productive qualities of laying hens during puberty - Gavrikov Andrey; Ostrenko Konstantin S. (BIO Web of Conferences)
The purpose of the study was to study the effect of coriander and fennel essential oils on the zootechnical and physiological indicators of productivity of laying hens during puberty, as well as on the health of laying hens against the background of the use of an essential oil supplement. The results of the study showed noticeable changes in the productive indicators of laying hens such as egg production, egg weight, egg composition. In addition, the condition of the animals was considered against the background of the use of the additive by weighing the animals and examining the parameters of the blood cell count. The use of additives of phytogens coriander and fennel by poultry did not reveal a negative effect on the body of laying hens by studying the growth and weight of poultry during the period from the beginning of the experiment and throughout its entire duration.